Pengembangan Pembelajaran Ekonomi Kreatif dalam Prakarya dan Kewirausahaan - Yuliati Sengkoen (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This research result of development aims 1) to produce effective learning set of creative economy to facilitate teacher and learners to create an interesting and meaningful learning process; 2) to describe the wotrhiness of the “Creative Economy in Workshop and Enterpreneurship” for Senior High School students. The learning set consists of syllabus, lesson plan, teacher guide books, and student work sheet. The reserach of development uses Design Based Research (DBR) approach which consist of 6 phases of development. Based on the results of validation of material experts, media experts, and practicioners show that the develop learning device is between 80%-100% with the validity level “valid”, which means the learning set can be used without revisions in very good criteria. The learning set tested to XI IS 4 students (individual, small group, and field trial) and the result is 91,65 which indicates that the learning set is worthy to be aplied. The supported by post test result of students itd average is 86,35.